The assessment of Metro Manila Development Authority's Intelligent Transportation System (ITS) - Dayao, Athena; Cruz, Edison (Quezon City University of the Philippines Diliman, 2015)
The Philippines has long suffered from traffic congestion especially in Metropolitan Manila. Projects implemented by Metro Manila Development Authority (MMDA) and other traffic governing agencies such as Traffic Engineering Center (TEC). Tratfic Management Agency (TMA), Department of Transportation and Communication (DOTC) and Land Transportation Office (LTO) had had been omnipresent. Billions of pesos are wasted on lost productivity, missed business opportunity, wasted fuel and additional air pollutants, not to mention other unquantifiable aspect such as the quality of life.
Intelligent Transportation System (ITS) is one of the solutions other countries had relied on in solving traffic congestion problem. This was introduced in the 1990s which has the goal of resolving road transportation issues such as traffic accidents and congestion through (Macababad & Regidor, 2009). For developed countries such as Japan and the United States, ITS is already considered as a matured technology while in the Philippines, it is only at its embryonic state. While one can argue that relying on ITS alone will not be sufficient to solve the perennial problem of traffic in the Metro, this paper aims to understand and identify the challenges and strengths of the ITS implemented by MMDA. The researcher believes that if the implementation of ITS will be a success then other government agencies can follow what MMDA had started. Currently, there are two ITS being used and deployed by MMDA. The first one is the State-of-the-Art Metro Manila Adaptive Responsive Traffic System (SMART) which uses Sydney Coordinated Adaptive Traffic System (SCATS) and the other is the state-of-the-art Traffic Signalization System (TSS) powered by Hermes technology. Interviews were conducted with project engineers : Francisco Pesino and Mario Melendez by the researcher using a targeted question approach. These were all recorded with the permission of the respondents. Research from secondary sources was also done to get a literature enough to understand how these ITS works. SWOT analysis was also done on these ITS. After careful analysis, the researcher came up with the conclusions as listed in the succeeding paragraph.
First, these ITS have a lot of potentials in terms of improving the exchange of information and using these information to benefit stakeholders such as the commuters, traffic enforcers and motorists. With big data and knowledge sharing on the rise, MMDA can further enhance the functionality of the Hermes technology. If integrated well, HERMES can be a source of a wealth of information that can be used to manage not only mobility but also efficient emergency handling procedure and other relevant issues concerning road management. However, the transfer of knowledge is not continuous and passive in nature. When Engineer Pesino was asked as to why up to now they have not tinkered with the machines or the technology they bought from outsource provider and try to improve it, just like what Korea did, he answered that they don't have enough capability nor funding to do so. In relation to that, MMDA's approach to technology evaluation is reactive. Unlike other developing Asian countries, the Philippines had not been known for its technology competency. Being in this position, it is important for our engineers and knowledge workers in MMDA realize to work on building their capability. The researcher believes that there's lack of progressive planning causing lapses in the operation. Lastly, the need for systematic and holistic approach is an absolute must. The researcher recommends that MMDA should have their own Research and Development (R&D) facility to maximize the use of technology in solving one of the Philippines problems which is traffic. MMDA should also be proactive in doing technology scanning so it can identify what will work best in the current profile of the country. Fore sighting and pre-planning should be done continuously as this is the only way we can measure up with other countries. We should also impose a systematic approach to problem solving. The efforts extended by MMDA so far had not been as fruitful but the move to use ITS is a good first step. It will be up to our traffic governing agencies and MMDA to take advantage of this technological leap.
Solution to a problem cannot be derived from jumping straight ahead to the solution without getting the root cause of the problem and clearly enumerating the steps needed to solve it. It is also time for the Philippine government to work on project such as these with highest urgency and prioritize this as this will drastically improve the quality of life of the Filipinos, not to mention the monetary return it may bring.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Intelligent Transportation System .